A Maximum Sustainable Growth Rate for British Industrial Outputs - Barker, T. S. (Review of Economic Studies, 1971)
Journal Article A Maximum Sustainable Growth Rate for British Industrial Outputs Get access T. S. Barker T. S. Barker University of Cambridge Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 38, Issue 3, July 1971, Pages 369–376, https://doi.org/10.2307/2296389 Published: 01 July 1971